P132 Significance of locus-specific TP53 mutations in ovarian cancer. (1st November 2019) - Knoll, K; Berger, A; Tsibulak, I; Leitner, K; Degasper, C; Welponer, H; Wieser, V; Marth, C; Fiegl, H; Zeimet, A-G
Abstract : Introduction/Background: The role of TP53 in tumor initiation and progression is widely studied. Depending on the histological subtype there are mutation rates in ovarian cancer (OC) of up to 95%. Most available studies assess the presence or absence of a TP53 mutation without taking into consideration the specific localisation and function of the mutation. The influence of exon specific TP53 mutations on the tumor biology was examined. Methodology: DNA samples from a total of 189 OC patients that had been diagnosed between the years of 1989 and 2014 were analysed using next-generation sequencing and the TruSight Cancer panel. Correlations between the presence of TP53 mutation and clinicopathological features were analysed using Chi-quadrat test. Survival analysis were performed with Kaplan-Meier and Cox regression. Results: Patients in the TP53 wild-type group demonstrated a statistically significant longer progression free survival (PFS) (p=0.003) and overall survival (OS) (p=<0.001) than those in the TP53-mutant group. In HGSOC a statistically significant difference in PFS of patients with tumors harbouring TP53 mutations in exons 1–5 compared with exons 6–8 (Median: 2.95 vs. 1.31 years) was revealed. A similar effect has been shown for the OS (Median: 3.62 vs. 3.01 years). However, cancers with TP53 mutations in exons 9–11 exhibited no difference in the PFS (p=0.87) and OS (p=0.78) when compared with TP53 wild-type cancers. Tumors with TP53 mutations with a risk of pathogenicity of >95% had a risk for progression (RR: 1.78; p=0.025), which was significantly higher in comparison to the wild-type cancers. Conclusion: This study revealed that different TP53 mutations have different effects on the biology of OC. Therefore accurate assessment of the locus-specific TP53 status in OCs is essential to understand their malignant phenotype and differences in chemotherapy responsiveness with the possibility to predict their clinical course. Disclosure: Nothing to disclose.